Inside Cover: A Versatile Chemoenzymatic Nanoreactor that Mimics NAD(P)H Oxidase for the In Situ Regeneration of Cofactors (Angew. Chem. Int. Ed. 39/2022). Issue 39 (19th September 2022) - Rodriguez‐Abetxuko, Andoni; Reifs, Antonio; Sánchez‐deAlcázar, Daniel; Beloqui, Ana
Abstract : A novel hybrid material that mimics NAD(P)H oxidase was designed and tested for the in situ regeneration of assorted enzyme cofactors, as reported by Ana Beloqui and co‐workers in their Communication (e202206926 ). This material was fabricated by the controlled assembly of glucose oxidase and hemin catalysts supported by a functional nanogel that allocates the (bio)catalysts in different compartments. The synthesis procedure allows for the fabrication of heterogeneous nanoreactors that were proven to be very effective for the in situ regeneration of natural and artificial enzyme cofactors.